Debt, Wealth and Climate Globally Coordinated Climate Authorities for Financing Green - Öncü, Ahmet; Sabri, T. Öncü (Economic and Political Weekly, 2020)
Based on the German Currency Reform of 1948 and the “Modern Debt Jubilee” of Steve Keen, a globally coordinated orderly debt deleveraging mechanism is proposed to address the global debt overhang problem is proposed. Since the global debt overhang and lack of sufficient climate finance flows are interconnected, Climate Authorities are added to the mechanism to discuss how this may help to improve the situation is discussed.